2014
DOI: 10.1016/j.jacc.2014.02.538
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma PCSK9 Level Is Equally Detrimental for Patients With Nonfamilial Hypercholesterolemia and Heterozygous Familial Hypercholesterolemia, Irrespective of Low-Density Lipoprotein Receptor Defects

Abstract: Elevated PCSK9 levels are equally detrimental for patients with HeFH or non-FH: a 100-ng/ml increase in PCSK9 will lead to an increase in LDL-C of 0.20 to 0.25 mmol/l in controls and HeFH alike, irrespective of their LDLR mutation. This explains why patients with non-FH or HeFH respond equally well to monoclonal antibodies targeting PCSK9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 29 publications
7
30
0
1
Order By: Relevance
“…Cell supernatants were cleared by centrifugation at 4°C for 10 min at 10,000 ϫ g. PCSK9 concentrations were measured in duplicate in supernatant from HepG2 and Huh7 cells with a SPC900 Quantikine enzyme-linked immunosorbent assay (ELISA) kit (R&D System, Lille, France), as described previously (23).…”
Section: Methodsmentioning
confidence: 99%
“…Cell supernatants were cleared by centrifugation at 4°C for 10 min at 10,000 ϫ g. PCSK9 concentrations were measured in duplicate in supernatant from HepG2 and Huh7 cells with a SPC900 Quantikine enzyme-linked immunosorbent assay (ELISA) kit (R&D System, Lille, France), as described previously (23).…”
Section: Methodsmentioning
confidence: 99%
“…4,12 We showed that ARH fibroblasts respond almost just as well to statins, PCSK9, and alirocumab than control fibroblasts, in terms of cell surface LDLR expression ( Figure …”
Section: Resultsmentioning
confidence: 84%
“…Circulating PCSK9 levels were extremely elevated in ARH at 526±31 ng/mL. 11,12 We first assessed cell-surface LDLR expression in lymphocytes isolated from control individuals and ARH patients by flow cytometry. After mevastatin treatment, ∆ mean fluorescence intensity (MFI) levels of cell surface LDLR expression reached a maximum of 635±56 arbitrary unit (AU) in control lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The authors compared ex vivo LDLR expression on the cell surface of lymphocytes (an accepted surrogate of hepatocyte LDLR expression) 17 in 22 HoFH patients with 1 normolipidemic individual and 5 HeFH patients. Experiments followed a rigorous sequence previously used by the authors 18 that simulate lipid-lowering treatments usually prescribed to FH patients, including stimulation of LDLR expression by 3-hydroxy-3-methylglutaryl-coenzyme reductase inhibition with mevastatin, incubation with recombinant PCSK9 to facilitate LDLR degradation, and incubation with a PCSK9 neutralizing antibody.…”
Section: See Accompanying Article On Page 592mentioning
confidence: 99%